DNA-based biosensor for the electrocatalytic determination of antioxidant capacity in beverages - Barroso, M. Fátima (2013)
Reactive oxygen species (ROS) are produced as a consequence of normal aerobic metabolism and are able to induce DNA oxidative damage. At the cellular level, the evaluation of the protective effect of antioxidants can be achieved by examining the integrity of the DNA nucleobases using electrochemical techniques. Herein, the use of an adenine-rich oligonucleotide (dA21) adsorbed on carbon paste electrodes for the assessment of the antioxidant capacity is proposed. The method was based on the partial damage of a DNA layer adsorbed on the electrode surface by OH• radicals generated by Fenton reaction and the subsequent electrochemical oxidation of the intact adenine bases to generate an oxidation product that was able to catalyze the oxidation of NADH. The presence of antioxidant compounds scavenged hydroxyl radicals leaving more adenines unoxidized, and thus, increasing the electrocatalytic current of NADHmeasured by differential pulse voltammetry (DPV). Using ascorbic acid (AA) as a model antioxidant species, the detection of as low as 50nMof AA in aqueous solution was possible. The protection efficiency was evaluated for several antioxidant compounds. The biosensor was applied to the determination of the total antioxidant capacity (TAC) in beverages.